Strategic planning for enhancing student competence in an Islamic boarding school - Kadir, Sitti Fatimah; Obaid, Muh. Yahya; Raehang; Rahmawati; Yahya, Nuruzzakiyyah; Rahmaniar (Institut Agama Islam Negeri Kendari, 2026)
This case study explored how strategic planning was designed and implemented to enhance student competence in a madrasah aliyah. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving school leaders, teachers, and students. Data were analyzed qualitatively. The findings revealed four major themes. First, strategic planning was vision-driven, providing clear direction for long-term educational priorities. Second, planning was collaborative, involving school leaders, teachers, and support staff in participatory decision-making. Third, strategic planning was translated into integrated curricular, extracurricular, and boarding programs. Finally, these integrated programs promoted students' cognitive, affective, and psychomotor competencies. The study conceptualizes strategic planning as a competency-development mechanism that links institutional vision, collaborative leadership, and integrated educational programs, offering practical implications for strengthening educational quality in Islamic boarding schools.